Analysis of Factors Affecting Primary Teachers' Happiness - Binsar Samosir; Darsih Idayani (Universitas Muhammadiyah Surakarta, 2022)
Teachers are indispensable to education. Teachers’ presence in the classroom is crucial for student learning. Consideration must be given to teachers’ happiness in order for them to perform their duties effectively in schools. This study employed a multiple linear regression model to determine the effects of character strength, social life, and compensation on the happiness of teachers. This was a quantitative descriptive study with 71 teachers as the population and 40 teachers as the sample from Maitreawira Primary School in Batam. The information was gathered using a questionnaire. Before using multiple linear regression to analyze the data, their validity and dependability were evaluated. The results indicated that the teachers’ social lives had an impact on their happiness. While the factors of moral fortitude and remuneration have a limited impact on teachers’ happiness, neither factor has a substantial impact. However, character strength, social life, and compensation can simultaneously affect teachers’ happiness. The headmaster of a primary school is expected to pay attention to the social life of teachers in order to increase their happiness. This study demonstrated the effect of character strength, social life, and compensation on the happiness of teachers.